2008
DOI: 10.1021/jo800335g
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Solandelactones A, B, E, and F Exploiting a Tandem Petasis−Claisen Lactonization Strategy

Abstract: Solandelactones A, B, E, and F were synthesized using Nozaki-Hiyama-Kishi coupling of iododiene 13 with aldehydes 14 and 99 obtained by oxidation of alcohols 92 and 94. Key steps in the synthesis of 92 and 94 were (i) a Nagao asymmetric acetate aldol reaction of aldehyde 77 with thionothiazolidine 78 to set in place an alcohol that becomes the (7 S) lactone center of solandelactones, (ii) a Simmons-Smith cyclopropanation of 80 directed by this alcohol, and (iii) Petasis methylenation of cyclic carbonate 90 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 49 publications
6
30
0
Order By: Relevance
“…This was achieved by utilizing the directing effect of the homoallylic alcohol with Ti(OiPr) 4 / tBuOOH [24] which, after acid-catalyzed rearrangement, gave solandelactone E as a single diastereoisomer in 68 % yield over two steps (Scheme 6). The spectroscopic data matched exactly with those of natural and synthetic solandelactone E. [1,[4][5][6] In conclusion, we have completed a short (13 steps, longest linear sequence) and highly selective synthesis of solandelactone E. The key steps included Sharpless epoxidation, Taber cyclopropanation, chemoselective reduction of a nitrile to an aldehyde, and our own lithiation-borylationallylation sequence on a highly functionalized substrate. Not only does the completed synthesis establish the method for application to complex targets, it also solves the problem of poor stereocontrol at C11 that had dogged many previous syntheses of this class of molecules.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…This was achieved by utilizing the directing effect of the homoallylic alcohol with Ti(OiPr) 4 / tBuOOH [24] which, after acid-catalyzed rearrangement, gave solandelactone E as a single diastereoisomer in 68 % yield over two steps (Scheme 6). The spectroscopic data matched exactly with those of natural and synthetic solandelactone E. [1,[4][5][6] In conclusion, we have completed a short (13 steps, longest linear sequence) and highly selective synthesis of solandelactone E. The key steps included Sharpless epoxidation, Taber cyclopropanation, chemoselective reduction of a nitrile to an aldehyde, and our own lithiation-borylationallylation sequence on a highly functionalized substrate. Not only does the completed synthesis establish the method for application to complex targets, it also solves the problem of poor stereocontrol at C11 that had dogged many previous syntheses of this class of molecules.…”
supporting
confidence: 57%
“…[3] Initial assignment of structure and absolute stereochemistry was based primarily on NMR studies, which led to two sets of compounds depending on their configuration at C11: R configuration for A, C, E, and G; S configuration for B, D, F, and H. However, the experimental data for synthetic solandelactone "F", which had been synthesized by Martin and coworkers, [4] matched the data for solandelactone E, thus indicating that the two sets of compounds had been incorrectly assigned. Further syntheses by White et al [5] as well as Pietruszka and Rieche [6] confirmed that the configuration at C11 in all of the solandelactones A-H should be depicted as in Scheme 1.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Our experiments showed that with borane methyl sulfide (BMS)-NaBH 4 , the chemoselective reduction of ester 3 could be achieved and gave the diol 4 in good yield, according to the literature precedents. [27][28][29][30][31] The reason for the chemoselectivity was discussed by Moriwake et al 54 The best ratio for BMS: NaBH 4 :ester 3 was 1:0.1:1. Excess BMS could lead to over-reduction and thus lower yield was obtained.…”
Section: Resultsmentioning
confidence: 97%
“…117 As shown in Scheme 1.76, Petasis methylenation of an enantiopure cyclic carbonate in tandem with a Claisen rearrangement generated the corresponding chiral octenalactone portion of solandelactones as a single stereoisomer in 60-65% yield. This chiral product was further converted into a mixture of expected solandelactones A, B, E and F.…”
Section: Miscellaneous Domino Reactionsmentioning
confidence: 99%